2019
DOI: 10.1186/s12862-019-1459-3
|View full text |Cite
|
Sign up to set email alerts
|

Widespread occurrence of asexual reproduction in higher termites of the Termes group (Termitidae: Termitinae)

Abstract: Background A decade ago, the mixed reproductive strategy Asexual Queen Succession (AQS) was first described in termites. In AQS species, the workers, soldiers and dispersing reproductives are produced through sexual reproduction, while non-dispersing (neotenic) queens arise through automictic thelytokous parthenogenesis, replace the founding queen and mate with the founding king. As yet, AQS has been documented in six species from three lineages of lower (Rhinotermitidae) and higher (Termitinae: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…We conducted a meta‐analysis of classical nymphs N3 and N4, and aspirants from all nests presented in Fournier et al (): (i) the sex ratio of classical nymphs N4 is balanced (205 individuals, 12 nests, sex ratio = 0.376 ± 0.270; one sample t ‐test; t = −1.595, df = 11, p = 0.139) in accordance with the sex ratio in alates (Hellemans, Fournier, Hanus, & Roisin in prep), while the sex ratio in aspirants is highly female‐biased (990 individuals, 40 nests, sex ratio = 0.835 ± 0.294; Wilcoxon rank sum test, W = 690.5, p < 0.001); (ii) female aspirants were mainly of parthenogenetic origin (92.2%, n = 193); and (iii) aspirants were found in almost all nests, including those containing alates (13 out of 17 nests), indicating that they develop independently of the massive nymphal production prior to dispersal. At several occasions, we observed directly aspirants molting into neotenics (Figure d–f).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We conducted a meta‐analysis of classical nymphs N3 and N4, and aspirants from all nests presented in Fournier et al (): (i) the sex ratio of classical nymphs N4 is balanced (205 individuals, 12 nests, sex ratio = 0.376 ± 0.270; one sample t ‐test; t = −1.595, df = 11, p = 0.139) in accordance with the sex ratio in alates (Hellemans, Fournier, Hanus, & Roisin in prep), while the sex ratio in aspirants is highly female‐biased (990 individuals, 40 nests, sex ratio = 0.835 ± 0.294; Wilcoxon rank sum test, W = 690.5, p < 0.001); (ii) female aspirants were mainly of parthenogenetic origin (92.2%, n = 193); and (iii) aspirants were found in almost all nests, including those containing alates (13 out of 17 nests), indicating that they develop independently of the massive nymphal production prior to dispersal. At several occasions, we observed directly aspirants molting into neotenics (Figure d–f).…”
Section: Resultsmentioning
confidence: 97%
“…Nymphoid neotenics were frequently found in nests of C. tuberosus , and their occurrence is most likely a normal step in the colony's life cycle (Fournier et al, ). Neotenics have been reported from several species in the clade comprising Cavitermes, its close relative Spinitermes , Palmitermes impostor , (see Hellemans et al, , ; Kyjaková et al, , for recent phylogenies): Spinitermes brevicornutus, S. nigrostomus (review in Noirot, ), S. robustus , S. trispinosus (Carrijo, ), Termes hospes (Noirot, ), T. laticornis , T. riograndensis (as T. saltans ; Noirot, ), and several Australian taxa probably part of the same clade: Xylochomitermes (as Termes ) occidualis , X. reductus , Hesperotermes infrequens (Gay, ), and Cristatitermes pineaformis , in which Miller () mentions two occurrences of multiple neotenic females with an imaginal king. Although the reports of neotenics are few, the ability to produce nymphoid neotenics, sometimes in the pattern very reminiscent of the AQS breeding system, appears widespread in this clade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQS was initially described from the Japanese Rhinotermitidae Reticulitermes speratus (Matsuura et al 2009), and later found in two additional species of Reticulitermes (Vargo et al Asexual queen succession in termites (A29115) 8 2012; Luchetti et al 2013). More recently, it was reported in several species of Termitidae belonging to Syntermitinae and Termitinae subfamilies (Fougeyrollas et al 2015;Fournier et al 2016;Fougeyrollas et al 2017;Hellemans et al 2019a). Because AQS occurs in phylogenetically distant taxa, in contrasted ecological contexts -in temperate wood-feeding subterranean Rhinotermitidae and in neotropical soil-feeding Termitidae-and under different modalities of ploidy restoration (see Genetic consequences of Asexual Queen Succession below), it appears clear that this breeding system evolved independently several times (Dedeine et al 2016;Matsuura 2017;Hellemans et al 2019a).…”
Section: Independent Origins Of Asexual Queen Successionmentioning
confidence: 99%
“…10–5 million years ago) and in North America (less than 14.1 million years ago) (Dedeine et al, ). Recent surveys of the breeding systems of higher termites (Termitidae) in French Guiana have repeatedly identified AQS in Neotropical termitids including Embiratermes neotenicus (Syntermitinae) (Fougeyrollas et al, ), the humivorous termite Cavitermes tuberosus (Termitinae) (Fournier, Hellemans, Hanus, & Roisin, ), Silvestritermes minutus (Syntermitinae) (Fougeyrollas et al, ) and Palmitermes impostor (Termitinae) (Hellemans et al, ). In all of these seven AQS species, the asexual neotenic queens derive from nymphs, that is, the sexual pathway.…”
Section: Genomic Imprinting Influences Caste Determination In Termitesmentioning
confidence: 99%